Heliostat field evaluation using ray tracing software - García-Lara, Héctor D.; Velázquez-Dominguez, Amir Alexander; Arriola-Gil, Yair Yosias; Garcia-Yera, Miguel (Renewable Energy, Biomass & Sustainability, 2021)
The ray-tracing method is commonly used for solar concentrator analysis. The simulation process consists of an initialization phase where all the input parameters are defined, followed by a simulation cycle that runs through all time instants to later move on to the final evaluation phase. The proposed method includes computational simulation, carrying out a study of the impact of two specific variables: (1) the distribution ratio of the heliostats given a fixed area and (2) the position of the target. The first being the ratio m:n that corresponds to the arrangement and distribution of the mirrors throughout the available area, where m represents the distance of the field along the East-West axis and n represents the distance of the field along the North-South axis. On the other hand, the target is placed on the northern edge of the heliostat field and only depends on its position on the East-West axis. The main interest is to determine where more energy is harvest by the heliostat field. It was shown through simulation in TracePro and results from processing in Matlab, that, for a location in Monterrey, NL, Mexico (25° N, 100° W) with an area of 75 m², an average of 100 kWh of energy can be harvest per day throughout the year with 72 mirrors of half a square meter each. This simulation was carried out using real direct radiation data.